Mewujudkan Keluarga Harmonis Peran Hukum Perkawinan Islam dalam Membangun Keluarga Ideal - Pulungan, Sofia Zuhro Zein; Harahap, Humaira Hananni; Pratiwi, Nurlila; Berliana, Raprila; Siregar, Galih Pratama; Iwan, Iwan (Pusdikra Publishing, 2024)
This article examines the significance of Islamic marriage law in fostering harmonious families, which are essential for a healthy society. Through a scientific approach, it highlights how Islamic marriage law establishes clear rights and obligations between spouses, emphasizing principles such as justice, effective communication, and shared responsibilities in child-rearing. These guidelines aim to create a loving and respectful family environment. However, the implementation of these laws faces challenges, including differing interpretations, cultural influences, and insufficient legal education. To overcome these hurdles, collaborative efforts are necessary to promote harmonious family dynamics. Practical steps suggested include nurturing the spirit of sakinah (tranquility), reviving mawaddah (love), and providing religious education to children. The article also addresses the protection of family members' rights through legal guarantees and educational services. By understanding and applying Islamic principles in daily life, families can achieve their ideal state as foundational units of a happy and prosperous society. Ultimately, the study aims to inspire Muslims to strive for families characterized by sakinah, mawaddah, and rahmah (compassion), making the dream of a harmonious family a tangible reality through consistent adherence to Islamic marriage law.